SOEP-IS 2016 - IDRM: Person-related data from innovative DRM module - DIW Berlin / SOEP (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Experiential measures of subjective well-being assess affective reactions over time, either by sampling experiences as they happen or by retrospectively recreating experiences soon after they occur. In this module, respondents reconstruct a full day, describing what they did, who they were with, and how they felt throughout the day.
Keywords: 330